Multisite photocatalytic depolymerization of lignin model compound utilizing full-spectrum light over magnetic microspheres - Chengcheng Suo; Wei Li; Sha Luo; Chunhui Ma; Shouxin Liu (iScience, 2023)
Summary: Photocatalytic depolymerization is a high value-added approach for utilization of lignin. In this study, magnetic microspheres of FeCoRu@SiO2–TiO2 were synthesized by a co-precipitation method. Doping with CoOx and RuOx was used to improve the response to visible light, and doping with TiO2 was used to improve the response to ultraviolet light (λ < 380 nm). The lignin model compound depolymerization rate was >90%. The electron paramagnetic resonance results showed that the reaction occurred in two steps (aerobic phase and oxygen-free phase). Most of the O2− was produced in the first step by cleavage of C-O bonds. The second step was inhibited in an oxygen-free atmosphere. This research provides a valid method for enhancing the photocatalytic properties using full-spectrum light and exploring the lignin photocatalytic depolymerization mechanism. Further research is required to develop the catalyst properties and performance to produce radicals.